2021
DOI: 10.3390/ma14206175
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Carbon and Carbon-Nitrogen Doped Black TiO2 Nanomaterials and Their Application in Sonophotocatalytic Remediation of Treated Agro-Industrial Wastewater

Abstract: The conventional open ponding system employed for palm oil mill agro-effluent (POME) treatment fails to lower the levels of organic pollutants to the mandatory standard discharge limits. In this work, carbon doped black TiO2 (CB-TiO2) and carbon-nitrogen co-doped black TiO2 (CNB-TiO2) were synthesized via glycerol assisted sol-gel techniques and employed for the remediation of treated palm oil mill effluent (TPOME). Both the samples were anatase phase, with a crystallite size of 11.09–22.18 nm, lower bandgap o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Doping with metal/nonmetal ions was employed to improve the catalytic activity of nanomaterials through numerous sonophotocatalytic degradation investigations. ,, Metallic dopants increase catalytic performance by forming impurity energy levels in the band gap. Equations and describe how incorporated metallic ions participate in the photocatalytic process of semiconductors.…”
Section: Nanostructured Sonophotocatalyst Enhancement Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Doping with metal/nonmetal ions was employed to improve the catalytic activity of nanomaterials through numerous sonophotocatalytic degradation investigations. ,, Metallic dopants increase catalytic performance by forming impurity energy levels in the band gap. Equations and describe how incorporated metallic ions participate in the photocatalytic process of semiconductors.…”
Section: Nanostructured Sonophotocatalyst Enhancement Strategiesmentioning
confidence: 99%
“…The pseudo-first order kinetics of a sonophotocatalytic reaction system can be described according to eq . Also, the E EO (kWh/m 3 ·order) for an AOP can be calculated by eq log true( false[ italicC 0 false] false[ italicC false] true) = 0.4343 K app t E EO = 1000 × P e × t 60 × V × log true( false[ italicC 0 false] false[ italicC false] true) where K app (min –1 ) is the pseudo-first order rate constant, P e denotes the input power of electrical-energy-consuming source (kW), V is the volume of the reaction solution (L), t represents time (s), and C and C 0 are the concentrations of pollutant at time t and 0, respectively.…”
Section: Electrical Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though some progress has been made in the field of TiO 2 -based UV light-shielding materials, several issues remain challenges. Due to the wide bandgap (3.0–3.2 eV), TiO 2 nanoparticles have limited UV absorption range (usually <380 nm) [ 15 ]. Moreover, high photocatalytic activity would accelerate the photodegradation of polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has been used as a post-treatment approach for the photodegradation of phenolic compounds from TPOM by just a few research groups [ 16 , 17 ]. For example, Nawaz et al [ 18 ] found that 180 min of visible light irradiation removed 48.17 percent of phenolic chemicals from TPOME using black TiO 2 .…”
Section: Introductionmentioning
confidence: 99%